Sporting Resilience During COVID-19: What Is the Nature of This Adversity and How Are Competitive Elite Athletes Adapting? - Gupta, Sahen; McCarthy, Paul Joseph (Frontiers in Psychology, 2021)
CoVid-19 pandemic is a global health issue which has severely disrupted and deferred several landmark international sporting competitions. Like the general population, athletes have faced direct psychological consequences from CoVid-19 in addition to cancellation of events, loss of support, lack of training, loss of earnings, hypervigilance and anxiety among others. The aim of the present research was to identify the adversity experiences of athletes caused by CoVid-19 (study 1) and explore the process of resilience used by competitive elite athletes for positive adaptation (study 2). Research has indicated psychological resilience to be a protective factor against similar adversities in the sporting context. The study uses an across-cases qualitative design comparing the real-time lived experiences of athletes during CoVid-19 using narrative analysis. Data was collected from 10 competitive-elite athletes from various countries as part of a larger doctoral dissertation study during the lockdown period using in-depth experiential interviews. Study 1 presents detailed description of adversity encounters and study 2 outlines the process of resilience as narrated by the participants framed in extant theory. We discuss recommendations for interventions and role of sports psychologists, coaches and sporting organisations in ensuring athlete mental health and the rehabilitation into post-CoVid sport life.